Participating in birth trauma Facebook groups: a hermeneutic phenomenology study of women’s experiences of online peer support following a traumatic birth - Cox, Serena (2023)
Background Traumatic birth experiences affect approximately one-third of women and can have significant long-term physical and mental health consequences. While women are known to participate in online support communities for birth trauma, their experiences within these remain unexplored.